Microfluidic Electrochemical Impedance Spectroscopy of Carbon Composite Nanofluids - Hye Jung Lee (Nature Portfolio, 2017)
Abstract Understanding the internal structure of composite nanofluids is critical for controlling their properties and engineering advanced composite nanofluid systems for various applications. This goal can be made possible by precise analysis with the help of a systematic robust platform. Here, we demonstrate a microfluidic device that can control the orientation of carbon nanomaterials in a suspension by applying external fields and subsequently examine the electrochemical properties of the fluids at microscale. Composite ﻿nanofluids were prepared using carbon nanomaterials, and their rheological, thermal, electrical, and morphological characteristics were examined. The analysis revealed that microfluidic electrochemical impedance spectroscopy (EIS) in the device offered more reliable in-depth information regarding the change in the microstructure of carbon composite nanofluids than typical bulk measurements. Equivalent circuit modelling was performed based on the EIS results. Furthermore, the hydrodynamics and electrostatics of the microfluidic platform were numerically investigated. We anticipate that this microfluidic approach can serve as a new strategy for designing and analyzing composite nanofluids more efficiently.